THE OPPOSITION TO THE HOME-RANCH IN THE CITY OF CÓRDOBA (ARGENTINA) BETWEEN THE 19TH AND 20TH CENTURIES - Suyai Pereyra, Ailen (2020)
This work analyzes the discursive context in which social housing is moralized by devaluing the figure of the “ranch” as the dominant habitability in popular neighborhoods of the city of Córdoba between 1880 and 1920. In this framework, the article reviews the intellectual and political debate and delimits habitability as an ideological sphere of intervention for subordinate sectors in Argentina. In this analytical work, the article proposes three vectors of analysis: the processes of alterization framed in the construction of the nation-state of the Latin-American region as ideological antecedents to the period; the role of the hygienist imaginary in Argentina that, linked to positivism, operated as a legitimate foundation to intervene in the popular habitat. Finally, as the condensation of the elements above, the meanings and valuations about the ranch-house in the province of Córdoba and its implications in Pueblo Nuevo as a popular neighborhood. The methodological strategy is based on the analysis of primary sources, political discourses and academic documents that were prepared by referents in the medical elite of the period. The result of the article presents the state of regulations on subordinate habitability to sanitary scope, the political discourse, and emerging public problem in the contradictions between secularization actions and the preceding colonial structuring.